The Designated Shipping Avoidance Area Around St. Lawrence Island, Northern Bering Sea, Is not Sufficient to Protect Foraging Habitat of the Island’s Breeding Seabird Community - Thiebot, Jean-Baptiste; Will, Alexis P.; Tsukamoto, Shota; Kitaysky, Alexander S.; Takahashi, Akinori (Frontiers in Marine Science, 2022)
One direct consequence of Arctic warming is the expansion of navigable portions of the Arctic Ocean. As a result, vessel traffic and the accompanying threats of spills, strikes and disturbance is intensifying throughout the Arctic. In the Bering Sea, these threats to the environment, wildlife and to the people who rely on marine resources for food and cultural continuity, are acute. We examined the spatial relevance of an Area To Be Avoided (ATBA), a shipping-risk mitigation measure, established around St. Lawrence Island with respect to seabirds, as sentinel species, habitat use. We studied four seabird species (common murre Uria aalge, thick-billed murre U. lomvia, crested auklet Aethia cristatella, black-legged kittiwake Rissa tridactyla) breeding at St. Lawrence Island in the northern Bering Sea. GPS tracking data from 47 at-sea foraging trips showed that both murre species and crested auklets distributed outside the ATBA, during at least one stage of the breeding season. A larger dataset based on the birds’ red blood cell isotopic signatures confirmed that for murres, the tracked individuals covered the broad niche exploited by these species. Habitat modelling further showed that the birds’ most suitable marine habitats were associated with seasonal surface chlorophyll blooms, and largely extended beyond the ATBA on the shelf north of the island. Data on the murres’ diet and diving behavior emphasized the importance of the shelf as a foraging habitat for these birds. We suggest that extending the ATBA to the north by only 35 km, would include areas of maximal habitat suitability. This extension would better protect seabirds, their foraging habitats and the cultural continuity of St. Lawrence Islanders, against growing threats stemming from Arctic warming.